Spatial changes in leaf biochemical profile of two tea cultivars following cold storage under two different vapour pressure deficit (VPD) conditions - Collings, Emma R.; Alamar, M. Carmen; Redfern, Sally P.; Cools, Katherine; Terry, Leon A. (Elsevier, 2018)
Withering is considered a crucial stage of black tea processing. In this study, tea shoots from two cultivars (cvs. Yabukita and Clone 2) were stored at 5 °C, in either a low or high vapour pressure deficit (VPD) environment, to determine the impact of different withering rates on physiology (viz. respiration rate [RR], colour and moisture loss) and biochemical profile (viz. individual catechins, methylxanthines) of tea shoots (Camellia sinensis). Low VPD and high VPD conditions during withering increased caffeine levels in Clone 2 and Yabukita, respectively (p < 0.05). Caffeine levels steadily increased over time in both cultivars (p < 0.05), coinciding with a rapid decline in theobromine (TB). Furthermore, stems contained lower epigallocatechin gallate (EGCG) and caffeine (ca. 75 and 56%, respectively) compared to bud and larger leaf (LL) (p < 0.05). Overall, the results of this study highlight factors such as mechanical harvesting, and hard or soft withering, which could affect final tea beverage quality.
Keywords: Catechins; Methylxanthines; Caffeine; Theobromine; Colour; Metabolic rate